1975
DOI: 10.1111/j.1432-1033.1975.tb02328.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an Alcohol‐Dehydrogenase–NAD(H)–Sepharose Complex Showing No Requirement of Soluble Coenzyme for Its Activity

Abstract: 1. Horse liver alcohol dehydrogenase and an NADH analogue, N6-[(6-aminohexyl)carbamoylmethyl]-NADH, have been co-immobilized to Sepharose 4B under conditions permitting binary complex formation between the enzyme and the cofactor.2. The enzyme-coenzyme-matrix preparations were assayed with a coupled oxidoreduction reaction and showed activities, prior to addition of coenzyme, that were up to 40 of that obtained in excess of free coenzyme.3. A molar ratio of 1 : 1 between the amount of bound nucleotide and boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The presence of NADH would also prevent formation of binary complexes between enzyme and any free NAD analogue. Such a complex could be imagined to co-immobilize and result in an active structure [12]. The reference system mentioned earlier, where native NAD was 'coupled' together with aminohexanol to alcohol dehydrogenase, resulted in a preparation which, before the second dialysis, contained as much coenzyme per subunit as the normal system did, The reference system, however, showed no internal activity whatsoever and the maximum activity declined to 37%, i.e.…”
Section: Enzymic Activity Of the Enzyme-coenzyme Complexmentioning
confidence: 99%
“…The presence of NADH would also prevent formation of binary complexes between enzyme and any free NAD analogue. Such a complex could be imagined to co-immobilize and result in an active structure [12]. The reference system mentioned earlier, where native NAD was 'coupled' together with aminohexanol to alcohol dehydrogenase, resulted in a preparation which, before the second dialysis, contained as much coenzyme per subunit as the normal system did, The reference system, however, showed no internal activity whatsoever and the maximum activity declined to 37%, i.e.…”
Section: Enzymic Activity Of the Enzyme-coenzyme Complexmentioning
confidence: 99%
“…In some report^^,^ it is not clear that this was done: for example, the concentrations of the soluble enzymes were not specified nor was the possibility that the stability of the soluble enzymes may have been affected by their concentration discussed. Gestrelius et al 4 found that soluble horse liver alcohol dehydrogenase was less stable than the immobilized enzyme at 5 0 T , but agreed that the low protein concentration in the soluble enzyme test may not have been optimal. These conditions were taken into account in the study presented here, an examination of some factors affecting the stability of horse liver alcohol dehydrogenase immobilized on inorganic supports.…”
Section: Introductionmentioning
confidence: 99%
“…The great similarity in spectroscopic properties of soluble and immobilised enzyme, as well as of their ternary complexes, shows that no significant conformational change has taken place during immobilisation. 4. Exchange of the non-catalytic Zn2 A rapidly increasing number of enzymes is being immobilised for various purposes by covalent binding to insoluble carriers, gel entrapment, crosslinking to membranes or other methods.…”
mentioning
confidence: 99%